Caracterizaciones de los principales derechos de protección de niñas, niños y adolescentes y su influencia en la prevención de infracciones en el cantón Montalvo - Rodríguez Pindolema, Pablo Efren (2020)
In this case study, it refers to the characterizations of the main protection rights of girls, boys and adolescents. In this sense, the following were investigated: survival rights, rights related to development, protection rights and participation rights; taking into consideration infractions such as: sexual violence, child pornography, adolescent abuse, inaccessibility to education, freedom of information, infringement of privacy, sale of narcotic drugs, sale of alcoholic beverages to minors, adoption of adolescents, domestic violence, adolescents involved in traffic accidents and child labor, etc. The study context is the Montalvo canton to determine the characterizations of the main rights and their influence on the prevention of infractions. For this, a survey based on the Likert questionnaire was used, which was applied to the members of the Cantonal Council for the Protection of Rights (CCPD) and the Cantonal Board for the Protection of Rights (JCPD). Obtaining as a result recurring infractions such as: sexual violence, free access to the internet, domestic violence, teenagers who drive cars causing traffic accidents, etc. Therefore, it is concluded to apply immediate solutions to the problems detected, through: development of driving programs for adolescents, guide on responsible use of the internet, awareness talks to promote a good family climate and joint action programs respectively, applying the principle of shared responsibility between the family and the state.